KAJIAN TEKNIS PEKERJAAN DETAIL ENGINEERING DESIGN (DED) PEMBANGUNAN GEDUNG INTENSIVE CARE UNIT (ICU) DAN KEBIDANAN RSUD KOTA DUMAI - Sugeng Wiyono; Yollyadriati, Yollyadriati; Vivi Ekayanti (Yayasan Nusantara Hasana Berdikari, 2025)
The Technical Study of the DED Work for the Construction of the ICU and Midwifery Building of Dumai City Regional Hospital was carried out based on a collaboration between PT. Tri Karsa and the Dumai City Regional General Hospital (RSUD). In accordance with the provisions outlined in the Terms of Reference (TOR), the series of works of the Technical Study of the DED for the Construction of the ICU and Midwifery Building of Dumai City Regional Hospital is a Preliminary Report which essentially contains a description of: the background of the work, work plan, consultant organization.